2014
DOI: 10.1071/mf13151
|View full text |Cite
|
Sign up to set email alerts
|

Is phytotoxicity of Phragmites australis residue influenced by decomposition condition, time and density?

Abstract: Phragmites australis is an invasive wetland plant and allelopathy appears to contribute to its invasiveness. We studied dynamics of physicochemical characteristics and phytotoxicity through residue decomposition of Phragmites with and without soil under different conditions and density over time. Physicochemical variables (water-soluble phenolics, dissolved organic carbon, specific ultraviolet absorbance, pH, electrical conductivity, osmotic potential and some anions, namely PO43–, Cl–, NO2–, NO3– and SO42–) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…In addition, significant decrease of the mycorrhizal infection and AMF spore density were found at sites of the highest compared with lowest Phragmites density. Additionally, higher phenolic content, lower pH and mycorrhizal inoculum potential of soil in high density sites demonstrate that Phragmites competitive success may be partly achieved due to release of allelopathic compounds; a finding compatible with other studies 11 , 14 , 34 , 46 48 . This study represents a step forward in our understanding of biodiversity indices and soil properties as affected by different degrees of Phragmites density, and provides valuable insights in advancing knowledge regarding the influence of different degrees of Phragmites density on soil microbial biomass and mycorrhizal inoculum potential.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, significant decrease of the mycorrhizal infection and AMF spore density were found at sites of the highest compared with lowest Phragmites density. Additionally, higher phenolic content, lower pH and mycorrhizal inoculum potential of soil in high density sites demonstrate that Phragmites competitive success may be partly achieved due to release of allelopathic compounds; a finding compatible with other studies 11 , 14 , 34 , 46 48 . This study represents a step forward in our understanding of biodiversity indices and soil properties as affected by different degrees of Phragmites density, and provides valuable insights in advancing knowledge regarding the influence of different degrees of Phragmites density on soil microbial biomass and mycorrhizal inoculum potential.…”
Section: Discussionsupporting
confidence: 87%
“…Photo‐degradation of phytotoxins produced by P. australis may induce severe phytotoxicity on other plant species such as Arabidopsis thaliana and Spartina patens (Rudrappa et al, 2009). Previous studies of P. australis regarding water extracts of organs (Uddin et al, 2012), root exudation (Rudrappa et al, 2007), and residue decomposition (Uddin et al, 2014b) have shown strong phytotoxic effects on germination, growth, and physiology of other plant species. The phenolic compound gallic acid has been identified in P. australis organs (Uddin et al, 2014a) and root exudates (Rudrappa et al, 2007), and it showed inhibitory effects on germination and growth of various species (Rudrappa et al, 2007).…”
mentioning
confidence: 99%
“…Density-dependent phytotoxicity stands in contrast to resource competition as increased growth of plants at low density is dependent on large part to the amount of resources available. Despite the allelopathic potential of P. australis on associated and model plant species, as shown by the growth of M. ericifolia , R. conglomeratus and L. sativa observed in this study was masked by the resource competition but the allelopathic effects of P. australis are well supported (Rudrappa et al 2007 ; Uddin et al 2012 , 2014a , b , c ). These studies showed that water extracts of different organs, residue decomposition and root secreted phytotoxins had negative effect on germination, growth, and development of other plant species.…”
Section: Discussionmentioning
confidence: 51%
“…Several studies have identified chemicals within P. australis organs which have antialgal, antifungal or antibacterial effects (Li and Hu 2005 ). Previous allelopathic studies have shown that water extracts, decomposed materials, root exudates and specific identified chemicals of P. australis organs have strong phytotoxic effects on germination, growth, and establishment of other plant species (Kettenring et al 2011 ; Rudrappa et al 2007 , 2009 ; Uddin et al 2012 , 2014a , b , c ) and thus, it is assumed that P. australis achieves its competitive advantages over invasion process into wetlands through allelopathy (Bains et al 2009 ; Rudrappa et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%